Design and Optimization of Mobile Learning Resources within the Framework of User Experience Oriented Educational Technology - Jing, Hou; Suartama, I Kadek; Parwati, Ni Nyoman (Universitas Pendidikan Mandalika, 2026)
This study aims to examine the effectiveness of designing and optimizing mobile learning resources within a user oriented educational technology framework in enhancing students’ learning engagement in higher education. The study employed a mixed methods approach with an explanatory sequential design. Participants were undergraduate students from Tianjin University of Technology selected through purposive sampling to ensure comparable academic backgrounds. Two intact classes were assigned as the experimental and control groups to maintain ecological validity. The experimental group consisted of 199 students, while the control group consisted of 200 students, resulting in a total sample of 399 participants (N = 399). Quantitative data were collected using validated scales measuring learning support, competence support, emotional support, learning self efficacy, learning engagement, were analyzed using ANCOVA, MANOVA, regression and mediation analysis. Qualitative data were obtained from learning behavior logs, classroom observations, and semi structured interviews and analyzed thematically. The results indicate that all three support dimensions significantly and positively influenced learning engagement, both directly and indirectly through learning self efficacy as a partial mediator. Learning support emerged as the strongest predictor of engagement, followed by competence and emotional support. These findings suggest that effective mobile learning is not determined by technological access alone, but by the quality of user-oriented learning experiences. This study provides empirical evidence that the MOVES framework offers a robust foundation for designing mobile learning resources that foster sustained engagement, self efficacy, and meaningful learning in digitally mediated higher education environments.